KUALITAS PELAYANAN ADMINISTRASI DI KANTOR DESA KAMPILI KAB. GOWA - Raudha, Ramadani Al; Ansari, Muh Isa; Rasdiana, Rasdiana (Universitas Muhammadiyah Makassar, 2023)
The purpose of this article is to find out the role of the village government in improving the quality of administrative services to the community at the Kampili Village Office. The type of research used in this research is descriptive with a qualitative approach, data collection techniques namely interviews, observation, and documentation. The research informants that were taken by the author were the Head of Kampili Village, the Village Secretary, the Head of Government Section, and the Kampili Village Administrative Services Section. The results of the study show the quality of Kampili village government services using Maswell's theory, namely 1) The services provided by staff and employees to the community are quite relevant and still need to be improved, 2) Availability and affordability of services provided by the Kampili Village government to the community can be implemented properly 3) Fair treatment with the distribution of a service provided by the village government without any system for individual communities or differentiating one community from other communities makes the community quite satisfied with the services provided, 4) It has become a priority in administrative services in Village Government by maximizing working apparatus and completing the facilities needed, 5) Kampili Village Government Services are quite efficient and affordable with no collection in services